Discordant immunization schedules can complicate vaccine evaluation for Europe (Italian Journal of Public Health, 2009)
Background: Most of the world’s vaccines are produced in Europe. Although vaccine licensure can becentralized through the EMEA, immunization recommendations are established at the national levels,reimbursement policies vary widely (ranging from regional to national, from private to public) and the lag timecan be long between licensure and eventual introduction into a national immunization program.Methods: An example of this discordance is the paediatric combination vaccines. Young infants in some EUcountries receive a whole-cell pertussis vaccine, in a three- to five-vaccine combination (“DTPw | IPV | Hib”).Acellular pertussis vaccines have been introduced over the last decade in many other EU countries, with four-to six-vaccine combinations (“DTPa | IPV | HBV | Hib”). Either of these combinations may be administered witha “3 + 1” schedule, with the first dose given between the age of 2 to 3 months, a spacing of 1 to 2 monthsbetween doses, and the final (booster) dose usually given at anywhere between 12 and 24 months of age, butin a handful of countries as late as the age of 3 to 5 years. By contrast, a “2 + 1” schedule is applied in somecountries for the “DTPa | IPV | Hib” or “DTPa | IPV | HBV | Hib” vaccines: first dose, 3 months old; spacing, 2months between doses; final (booster) dose, 11 to 14 months of age.Results: Differing national policies in the EU may have led to delays in the introduction of the newest vaccines(e.g., pneumococcal conjugate, meningococcal conjugate, rotavirus, influenza, varicella-zoster, etc.) thatmust be shown to be compatible with the various infant immunization programs across Europe. This coulddelay the likelihood, in some EU countries, of the public health advancements that these new vaccines canprovide.Conclusions: Sharing of best practices from vaccination schedules might rationalize vaccine development,streamline the introduction of novel vaccines into the national immunization programs, and facilitate theevaluation of the impact of new vaccines in Europe.
Keywords: European Union; immunization programs; pneumococcal vaccines; rotavirus vaccines; papillomavirus vaccines